SCALES OF HORIZONTAL DISLOCATIONS IN URALIAN VARISCIDES AND EARLY KIMMERIDES - Chuvashov B.I.; Shcherbakov O.A. (My University, 2007)
The issue of the establishment of the primary sedimentary surface in fold belts is directly related to reconstruction of the real geological history of a particular region. The most popular method of such reconstructions is based on compilation of geological cross sections with their subsequent straightening. Estimation of real values is always complicated by the incompleteness of material and the presence of fractures. To estimate the scale of horizontal displacements in particular areas, we applied an original method based on some laterally sustained and unambiguous facies or paleotectonic boundaries. In order to reconstruct areas of the initial accumulation surface of Upper Devonian–Lower Carboniferous sediments on the western slope of the Middle Urals, we examined the walls of the Kama–Kinel system of troughs, which are reliably traced based on reefal limestones of the Askyn Formation for the Frasnian Stage. Reefal microbial and algal limestones of the Storozhevsk Formation were used for the Famennian Stage. For Tournaisian sediments, thick-bedded and massive limestones were analyzed. Transitional zones between these section types are narrow. Therefore, their influence on the quantitative parameters is negligible.
Keywords: Paleozoic::Devonian::Upper::Famennian; Paleozoic::Carboniferous::Mississippian::Lower::Tournaisian; Палеозой::Девонская::Верхний::Фаменский; Палеозой::Каменноугольная::Нижний::Турнейский